The neuro-consumer : adapting marketing and communication strategies for the subconscious, instinctive and irrational consumer's brain /: adapting marketing and communication strategies for the subconscious, instinctive and irrational consumer's brain. (2020) - Bayle-Tourtoulou, Anne-Sophie; Badoc, Michel
No abstract available